2019
DOI: 10.1002/aqc.3134
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the population size and dynamics of the British grey seal

Abstract: 1. Grey seals (Halichoerus grypus) were the first mammals to be protected by an Act of Parliament in the UK and are currently protected under UK, Scottish, and EU conservation legislation. Reporting requirements under each of these statutes requires accurate and timely population estimates. Monitoring is principally conducted by aerial surveys of the breeding colonies; these are used to produce estimates of annual pup production. Translating these data to estimates of adult population size requires information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 40 publications
3
82
0
Order By: Relevance
“…show different dynamics to those of harbour seals (Russell, Morris, Duck, Thompson, & Hiby, 2019;Thomas et al, 2019). Both pup production and population estimates for grey seals in the West Scotland and the Western Isles SMUs were increasing until the mid-1990s…”
Section: Robustness Of Trendsmentioning
confidence: 96%
“…show different dynamics to those of harbour seals (Russell, Morris, Duck, Thompson, & Hiby, 2019;Thomas et al, 2019). Both pup production and population estimates for grey seals in the West Scotland and the Western Isles SMUs were increasing until the mid-1990s…”
Section: Robustness Of Trendsmentioning
confidence: 96%
“…This indicates that population dynamics are being driven by density-dependent processes and that the populations are at or nearing carrying capacity (Thomas et al, 2019). Combining this pup production time-series with an independent estimate of population size (Lonergan, Duck, Thompson, Moss, & Mcconnell, 2011;Russell, Duck, Morris, & Thompson, 2016), within an age-structured population model, has revealed that the main density-dependent effect is likely acting through increased pup mortality (Thomas et al, 2019). How pup production and its trends relate to estimates of population size and trajectories is dependent on fecundity and age-sex-specific survival, and changes therein.…”
Section: Overall Trends In Pup Productionmentioning
confidence: 99%
“…Thus, pup survival may still be driven by density-dependent processes acting on females, as well as those acting directly on pups. Regional population trends are discussed in Thomas et al (2019). Regional population trends are discussed in Thomas et al (2019).…”
Section: Overall Trends In Pup Productionmentioning
confidence: 99%
See 2 more Smart Citations